2014
DOI: 10.1007/s00705-014-2227-8
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequences of two biologically distinct isolates of Asparagus virus 1

Abstract: The complete genome sequences of two asparagus virus 1 (AV-1) isolates differing in their ability to cause systemic infection in Nicotiana benthamiana were determined. Their genomes had 9,741 nucleotides excluding the 3'-terminal poly(A) tail, encoded a polyprotein of 3,112 amino acids, and shared 99.6 % nucleotide sequence identity. They differed at 37 nucleotide and 15 amino acid sequence positions (99.5 % identity) scattered over the polyprotein. The closest relatives of AV-1 in amino acid sequence identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Among the German AV1 isolates, two pathotypes have been identified that differed in their ability to infect Nicotiana benthamiana (Rabenstein et al, 2007). On the molecular level, 37 non-synonymous nucleotide substitutions, resulting in 15 amino acid sequence differences, spanning the whole coding region were identified between them (Blockus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among the German AV1 isolates, two pathotypes have been identified that differed in their ability to infect Nicotiana benthamiana (Rabenstein et al, 2007). On the molecular level, 37 non-synonymous nucleotide substitutions, resulting in 15 amino acid sequence differences, spanning the whole coding region were identified between them (Blockus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%